2011
DOI: 10.1128/aem.02952-10
|View full text |Cite
|
Sign up to set email alerts
|

Differing Growth Responses of Major Phylogenetic Groups of Marine Bacteria to Natural Phytoplankton Blooms in the Western North Pacific Ocean

Abstract: Growth and productivity of phytoplankton substantially change organic matter characteristics, which affect bacterial abundance, productivity, and community structure in aquatic ecosystems. We analyzed bacterial community structures and measured activities inside and outside phytoplankton blooms in the western North Pacific Ocean by using bromodeoxyuridine immunocytochemistry and fluorescence in situ hybridization (BIC-FISH). Roseobacter/Rhodobacter, SAR11, Betaproteobacteria, Alteromonas, SAR86, and Bacteroide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
115
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 74 publications
13
115
0
Order By: Relevance
“…The initial seawater contained a natural assemblage of bacteria and the added cultures of Alteromonas spp. bacteria (Table 2) each contained less than 10% of the total number of bacteria already present in the mesocosm, similar to the proportion of Alteromonas to total heterotrophic bacteria found in a phytoplankton bloom in the North Pacific [Tada et al, 2011]. A final aliquot of ZoBell media, a culture of the heterotrophic bacterium Pseudoalteromonas atlantica (strain 19262), and a culture of Dunaliella tertiolecta (green algae) were added to the wave channel, bringing chl a concentrations up to 5.5 mg m À3 .…”
Section: Preparation and Addition Of Biological And Organic Mattermentioning
confidence: 91%
“…The initial seawater contained a natural assemblage of bacteria and the added cultures of Alteromonas spp. bacteria (Table 2) each contained less than 10% of the total number of bacteria already present in the mesocosm, similar to the proportion of Alteromonas to total heterotrophic bacteria found in a phytoplankton bloom in the North Pacific [Tada et al, 2011]. A final aliquot of ZoBell media, a culture of the heterotrophic bacterium Pseudoalteromonas atlantica (strain 19262), and a culture of Dunaliella tertiolecta (green algae) were added to the wave channel, bringing chl a concentrations up to 5.5 mg m À3 .…”
Section: Preparation and Addition Of Biological And Organic Mattermentioning
confidence: 91%
“…(Bell et al 1974, Lau et al 2007, Moreira et al 2011, Tada et al 2011, Trabelsi & Rassoulzadegan 2011, Nelson & Carlson 2012, Sarmento & Gasol 2012, Gómez-Consarnau et al 2012. Testing a diverse suite of DOM sources prepared in various ways allowed for investigating response dynamics of individual bacterioplankton strains to DOM sources of distinct size, chemistry and origin.…”
Section: Resultsmentioning
confidence: 99%
“…Using fluorescence in-situ hybridization, Yan et al (2009) Increased abundance of OM60 cells has also been shown to co-occur with algal blooms (Eilers et al, 2001;Alonso-Sáez et al, 2007;Yan et al, 2009) and many studies demonstrate that diverse low abundance taxa bloom under increasing concentrations of organic nutrients Eilers et al, 2000;Romera-Castillo et al, 2011;Tada et al, 2011;Nelson and Carlson, 2012). These opportunistic taxa exhibit a "feast or famine" lifestyle (Nissen, 1987;Flärdh et al, 1992;Srinivasan and Kjelleberg, 1998) and are often referred to as copiotrophs (Lauro et al, 2009;Yooseph et al, 2010).…”
Section: Om60 Cladementioning
confidence: 99%
See 2 more Smart Citations